Description of Neuroandricus a new genus of gall wasp (Hym.: Cynipidae) and a new species of associated Sycophila (Hym.: Eurytomidae) - Pujade-Villar, Juli; Savall-Roig, Gabriel; Equihua-Martínez, Armando; Estrada-Venegas, Edith G.; Barrera-Ruiz, Uriel M.; Cibrián-Tovar, David; Vera-Ortiz, Alexis; Romero-Rangel, Silvia; Cuesta-Porta, Víctor; Cazorla-Vila, Júlia; Melika, George (Zootaxa, 2024)
A new genus of oak gall wasps, Neuroandricus Pujade-Villar & Melika, gen. nov., with one new species, N. pustulatus Pujade-Villar & Melika, sp. nov. is described from Mexico. The new Cynipini species is known from its asexual generation which induces galls on leaves of Quercus (section Quercus). Also, a new species of gall-associated parasitoid is described, Sycophila baldufi Savall-Roig & Pujade-Villar, sp. nov. (Eurytomidae), emerged from N. pustulatus galls. Diagnosis, distribution and biological data of the new species are given.